2019
DOI: 10.1186/s13063-018-3145-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the analgesic effect and advantage of transcutaneous electrical acupoint stimulation combined with opioid drugs for moderate to severe cancer-related pain: a study protocol for a randomized controlled trial

Abstract: BackgroundTranscutaneous electrical acupoint stimulation (TEAS), which is also known as acupuncture-like transcutaneous electrical nerve stimulation (TENS), has been widely used in acute or chronic pain. However, previous research has not demonstrated that TEAS is effective for cancer-related pain. Opioid drugs are strongly recommended for treating cancer-related pain, but opioid-induced immunosuppression is still the most intractable drug-induced medical problem. Evaluating the efficacy and potential advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This contrast in practice and belief may represent an area for improvement and advocacy and warrants further study to determine if underlying bias or sympathy for cancer patients is affecting actual prescribing practices [11]. This is similar to other studies that found that cancer patients were more likely to have an opioid prescription than a non-cancer patient and that they are at high risk for opioid misuse [9][10][11].…”
Section: Discussionsupporting
confidence: 75%
“…This contrast in practice and belief may represent an area for improvement and advocacy and warrants further study to determine if underlying bias or sympathy for cancer patients is affecting actual prescribing practices [11]. This is similar to other studies that found that cancer patients were more likely to have an opioid prescription than a non-cancer patient and that they are at high risk for opioid misuse [9][10][11].…”
Section: Discussionsupporting
confidence: 75%
“…A meta-analysis including a total of 1,350 participants demonstrated that the use of TENS could significantly reduce the consumption of postoperative analgesics ( 42 ), whereas TEAS combined the effect of TENS and acupuncture. In addition, Liang et al ( 43 ) reported that TEAS was an effective adjunct to opioid therapy for moderate and severe cancer-related pain, and could reduce side effects and improve immune function. Therefore, the utilization of TEAS may have a direct clinical application value, especially for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture and moxibustion therapy are used as complementary therapy in China and abroad for its effectiveness, simplicity and fewer adverse reactions. Other modifications of acupuncture methods, such as percutaneous electrical stimulation [ 20 ] and electroacupuncture [ 21 ] have been established. The main indication for acupuncture and moxibustion is pain.…”
Section: Discussionmentioning
confidence: 99%